Słowa wsobne i zasobne w czasie i przestrzeni - Wesołowska, Elżbieta (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
The author focuses her attention on various examples of maxims and aphorisms mainly in two aspects. The first aspect is connected with the construction of so called ”winged sentences" on the grounds of the opposition between written and oral or visual forms. Such a contrast may lead to sophisticated literary play, but sometimes causes misunderstanding or at least an ambiguity of meaning in relation to the aphorism. The second aspect concerns the inner construction of the maxims which refer to themselves or provoke further intertextual dialogue.
Keywords: aforyzmy; grafika; oralność społeczna; media